INTEGRATING AI IN ARCHITECTURAL DESIGN THINKING : AN OPPORTUNITY AND CHALLENGES STUDY IN INDONESIA ARCHITECTURAL EDUCATION - Dharmatanna, Stephanus Wirawan; Wijaya, Elvina Shanggrama; Pramananda, I Putu Bagus (architecture department, Engineering faculty, Universitas Diponegoro, 2025)
The presence of AI has been integrated into many aspects of life, including education and even architecture. AI has offered revolutionary alternatives for analyzing, optimizing, and visualizing an architectural design that can enrich learning experiences for students in architecture studios. Nevertheless, there is still a little research done regarding the potential and threat that AI could conceive, especially in Indonesia. The purpose of this study is to explore the use of AI in architectural education through different stages of the design process. A literature review regarding the use of AI is done to determine the variety of AI used in architecture. A questionnaire is then distributed to lecturers and students that have already used digital architecture. This research could illustrate the role that AI plays in an architectural design studio.